2017
DOI: 10.3382/ps/pew395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varying dietary concentrations of lysine on growth performance of the Pearl Grey guinea fowl

Abstract: Lysine is the second limiting essential amino acid in poultry nutrition after methionine. Understanding the lysine requirement of poultry is necessary in guiding formulation of least cost diets that effectively meet the nutritional needs of individual birds. The lysine requirement of the Pearl Grey guinea fowl (PGGF) is not known. Therefore, the objective of this study was to assess the appropriate lysine levels required for optimal growth attributes of the PGGF. In a 12-week study, 512 one-day-old Pearl Grey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…This study revealed adverse outcomes, such as decreases in the initial body weight, BWG, feed intake and feed efficiency, in chickens fed low lysine concentrations. This finding was consistent with that of Bhogoju et al [ 5 ], who reported that a low (80% NRC) concentration of lysine in diets decreased the BW and feed intake of broilers compared with the high (120% NRC) or NRC-recommended (100%) lysine concentration intake. Nasr and Kheiri [ 3 ] also reported that decreasing lysine concentration in feed from 1.14% to 0.8% decreased the body weight, BWG and feed intake of broilers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study revealed adverse outcomes, such as decreases in the initial body weight, BWG, feed intake and feed efficiency, in chickens fed low lysine concentrations. This finding was consistent with that of Bhogoju et al [ 5 ], who reported that a low (80% NRC) concentration of lysine in diets decreased the BW and feed intake of broilers compared with the high (120% NRC) or NRC-recommended (100%) lysine concentration intake. Nasr and Kheiri [ 3 ] also reported that decreasing lysine concentration in feed from 1.14% to 0.8% decreased the body weight, BWG and feed intake of broilers.…”
Section: Discussionsupporting
confidence: 92%
“…This shows that growth is highly impaired when the concentrations of lysine are significantly reduced, hence causing the deaths of broiler chickens. Similar studies by Nasr and Kheiri [ 3 ], Bhogoju et al [ 5 ], Khwatenge et al [ 6 ], Kerr et al [ 40 ] and Corzo et al [ 41 ] have confirmed this effect of lysine on the growth performance of birds. The reduction in feed intake may likely be due to the birds experiencing satiety effects, hence reducing growth [ 4 , 11 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results obtained are in agreement with the findings of Kamisoyama et al ( 2009); Widyaratne and Drew (2011) who indicated that higher dietary Lys resulted in increasing nutrient digestibility in ducks. It was due to in dietary low Lys levels, the ducks have a higher ratio of facing deficiency in diets, thus the ducks have to stimulate consumption and digestion to overcome the deficiency (Bhogoju et al, 2017). Besides, ducks fed dietary sufficient ME could accumulate the protein and utilize feed efficiently (Aftab, 2019).…”
Section: Comparing Nutrient and Amino Acid Digestibility Values Between 8 And 10 Weeks Of Age Of Local Muscovy Ducksmentioning
confidence: 99%
“…The digestibilities of nonessential amino acids in the experiment were equivalent to the results ofKong and Adeola (2014) with the values of alanine, aspartic, glutamic, glycine, proline, serine and tyrosine which were 83,7; 83.0, 88.3, 78.2, 93.5, 89.9 and 91.6%, respectively. It was supported by the studies ofBhogoju et al (2017) who indicated that the supplementation of Lys in the diets enhanced the amino acid digestibility in poultry. The increase Lys in diet could increase the digestibility of other amino acids in the diet(Sharma et al, 2018).…”
mentioning
confidence: 93%